Sejarah Perkembangan LAZISMU Kota Surabaya 2007-2019 M - Fauzi Fadli Habibie (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2019)
Abstract: This is an article that discusses the history of the amil, zakat, infaq and shodaqoh institutions owned by Muhammadiyah. Researchers provide limitations on three things, namely: (1). What is the history of the establishment of LAZISMU Surabaya City (2). What is the dynamics of LAZISMU's development from 2007-2019 (3). What are the supporting and inhibiting factors in the development of LAZISMU. The writing of this article was compiled using historical research methods with four steps, namely heuristics, verification, interpretation and historiography. The approach used is a historical approach from a diachronic perspective (describing events that occurred in the past chronologically in the time dimension). While the theory used to analyze is the theory of sociology, namely John Obert Voll; Continuity and Change and Arnold J. Toynbee; Challenge and Response. From the results of the research conducted, it can be concluded that: (1) LAZISMU Surabaya City was established in 2007 AD starting from the fields of waqf, zakat, infaq, and sadaqah (ZIS) Muhammadiyah based on a meeting of members of the Muhammadiyah Regional Leadership Surabaya City at the Muhammadiyah Ngagel Branch Office, Surabaya. (2) LAZISMU has developed, both in terms of the number of donors, work programs and facilities and infrastructure. (3) LAZISMU's supporting factors are being sheltered by a large organization, having a clear legal entity, being trustworthy, accountable and transparent. Meanwhile, the inhibiting factors for LAZISMU are the lack of human resources, the large number of competitors for zakat institutions in Surabaya who do not have their own offices. Keywords: lazis, Muhammadiyah, development